MFAP4 as a novel biomarker for predicting liver fibrosis and prognosis in infants with biliary atresia through the integration of bioinformatics with clinical data analysis - Yang, Chunxiao; Zhan, Jianghua (Frontiers in Pediatrics, 2025)
BackgroundBiliary atresia (BA) is a progressive obliteration of intrahepatic and extrahepatic bile ducts. Our study aimed to identify and validate hub genes that are differentially expressed in BA, and to investigate their relationship with liver fibrosis.MethodsThe BA microarray datasets GSE46960 and GSE15235 were downloaded from the Gene Expression Omnibus (GEO) database. Clinical BA liver tissue samples were collected for quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and western blotting (WB). Serum samples were analyzed for MFAP4 content using enzyme-linked immunosorbent assay (ELISA), and the corresponding clinical data of pediatric patients were collected. The relationship between serum MFAP4 levels and liver fibrosis, as well as prognosis, was investigated using ROC curve analysis. Furthermore, Kaplan–Meier (KM) curves were used to validate the prognostic significance of MFAP4 levels.ResultsThrough bioinformatics analysis and experimental validation, MFAP4 was identified as a hub gene. MFAP4 via PCR and immunohistochemistry is significantly upregulated in biliary atresia compared to total functional cyst liver tissue. Serum MFAP4 levels accurately reflects the degree of liver fibrosis in patients with BA. High serum MFAP4 levels predicted a poorer native liver survival rate one year after Kasai surgery.ConclusionsWe discovered that MFAP4 is a crucial BA-associated gene, and validated its expression in BA. Furthermore, serum MFAP4 levels may serve as predictive markers for the degree of liver fibrosis and autologous liver survival after Kasai surgery.